Assessment of agroforestry residue potentials for the bioeconomy in the European Union. (1st March 2018) - Thorenz, Andrea; Wietschel, Lars; Stindt, Dennis; Tuma, Axel
Abstract: The biobased chemical industry is characterised by strong growth. Innovative products and materials such as biopolymers have been developed, and current European demand for biopolymers exceeds the domestic supply. Agroforestry residues can serve as main sources of the basic building blocks for chemicals and materials. This work assesses sustainably available agroforestry residues to feed a high added-value materials and product bioeconomy. To evaluate bioeconomic potential, a structured three-step approach is applied. Cultivation practices, sustainability issues, legislative restrictions, technical limitations and competitive applications are considered. All data regarding bioeconomic potential are processed on a regional level and mapped by ArcGIS. Our results identify wheat straw as the most promising source in the agricultural sector, followed by maize stover, barley straw and rape straw, which all contain a total concentration of lignocellulose of more than 80% of dry matter. In the forestry sector, residue bark from two coniferous species, spruce and pine, is the most promising source, with approximately 70% lignocellulose. Additionally, coniferous bark contains considerable amounts of tannin, which has attracted increasing interest for industrial utilisation. A sensitivity analysis concerning removal rates, residue-to-crop ratios, changes in farming technologies and competing applications is applied at the end of the study to consolidate our results. Highlights: The bioeconomic potential of agricultural residues adds up to more than 107 Mt. Wheat straw is most important lignocellulose residue in the EU. Approximately only 8% of agricultural residues are contemporarily exploited. Coniferous bark can be important for the bioeconomy with a potential of 14 Mt.